THE EFFECTIVENESS OF WEB-BASED APPLICATIONS IN ENHANCING ENGLISH LANGUAGE SKILLS FOR MEDICAL STUDENTS (Modern education and development, 2025)
This study investigates how well web-based tools can help medical students' English language proficiency. Given the significance of English in clinical communication and medical research, medical students must become highly proficient in the language. Students improved their medical English vocabulary, grammar, and communication skills during a six-week period by using programs like Lingvist, Meducation, and BabelMed. Surveys, instructor feedback, and pre- and post-assessments were used to collect data. The findings showed notable gains in clinical communication abilities, reading comprehension, and word retention. Additionally, students said they felt more comfortable using medical English in clinical and academic contexts. The study comes to the conclusion that web-based applications are useful resources for enhancing conventional language training because they provide individualized learning opportunities that aid in students' language development in a medical setting.